Control, Simulation, and Monitoring of Thermal Processes in Power Plants - Madejski, Pawel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue aims to cover the recent research results being developed, both theoretically and experimentally, on the laboratory, pilot, and industrial scale about thermal processes in power plants. This reprint focuses on thermal and flow processes and their impact on highly efficient and low-emission electricity generation and heat production in thermal power plants. Special attention is given to steam condensers and separators for application in thermal power plants, development systems and tools for heat production forecasting in combined heat and power plants, presenting such ideas as the negative CO2 emission gas power plant cycle and production of gas fuels by sewage sludge gasification as well as about methods and techniques for CO2 capture. The research investigation results can find implementation in real-scale power technologies such as steam power plants, gas power plants, nuclear power plants, and hybrid power plants based on renewable energy sources.